PENGARUH ALOKASI DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA CINTA DAMAI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Fitri, Fitri; Munthe, Marabona (Komunitas Manajemen Kompetitif, 2025)
This research is theoretically sourced from the Government Regulation of the Republic of Indonesia Number 43 of 2014 concerning the Implementation of Law Number 6 of 2014 concerning villages which defines that Village Fund Allocation is the balance received by the Regency/City Government in the Regency/City Regional Revenue and Expenditure Budget after deducting special allocation funds. And According to Law Number 11 of 2009 concerning social welfare article 1 paragraph 1 it is stated that social welfare is a condition of fulfilling material, spiritual, and condition needs of citizens so that they can live decently and are able to develop themselves, so that they can carry out their social functions. The method used in this research is a quantitative method. The types of data sources used are secondary data and primary data, the population in this study was 1,555 people and the sample selected was 94 people with incidental sampling techniques in the form of distributing questionnaires, conducting interviews and observations. The results of this research and discussion of this research indicate that there is an influence of fund allocation on the welfare of village communities. The R square value shows that 18.3% of the level of community welfare can be explained by the village fund allocation variable and the remaining 81.7% is explained by other variables that influence the welfare of the people of Cinta Damai Village, Tapung Hilir District, Kampar Regency. Keywords: Funds, Village, Welfare, Community